ETHNO-BOTANICAL STUDIES FROM NORTHERN PAKISTAN - Afzal, Saadia; Afzal, Naeema; Awan, Mohammad Rashid; Khan, Taher Salim; Gilani, Aneel; Khanum, Rizwana; Tariq, Sumbal (Journal of Ayub Medical College Abbottabad, 2009)
Background: In this research paper efforts have been made to document the ethno-botanical knowledge of important plant species found in Northern Pakistan. It includes Thandiani, Galiat, Kaghan, Swat, Buner, Dir, Chitral and Northern Areas of Pakistan. The area has many climatic and vegetation zones or biomes. Locals residing in mountainous areas belonging to various ethnic groups are traditionally utilizing plants over many generations; these ethnic groups have their distinct life style, belief, traditions and cultural heritage. Methods: Plant collection and data regarding traditional uses in various areas of Northern Pakistan has been done periodically in different flowering /fruiting seasons. Locals of old age belonging to various ethnic groups were personally interviewed for establishing uses of plants. Photography is done for easy identification and habitat recognition. Collected plant specimens and seeds were preserved. Plant species were dried, mounted, identified and authenticated. Result: 135 genera belonging from 66 families of angiosperms and gymnosperms were studied and described.76 species were known to have traditional and ethno botanical uses. Plants have been utilized for many generations. Ethnic groups have distinct life style and have different economic uses for these plants. Due to unsustainable exploitation of natural habitats scarcity of drug plants has occurred. As consequence some species are depleting and may become extinct in near future, e. g. Morchella esculenta, Colchicum lueteum and Viola serpens are just a few of these. Conclusion: Although some sporadic information is available about the flora of this region but very little documented record of the ethno-botanically important plants has been established. It is expected that this research paper will be beneficial for students, researchers, farmers, foresters and general public. On the basis of data obtained it is concluded that ethno-botanical Flora of Northern Pakistan is quite rich and is diverse, due to the difference in altitude, climate and other topographic conditions. Keywords: Ethno botanical study, Northern Pakistan, Drug Plants